Method validation for pesticide multiresidue analysis of pyrethroid on green beans of arabica gayo coffee using gas chromatography-electron capture detector (GC-ECD). Issue 1 (February 2021) - Yusuf, M; Idroes, R; Saiful; Lelifajri; Bakri, T K; Satria, M; Nufus, H; Yuswandi, I; Helwani, Z; Muslem; Marlina
Abstract: The method validation for the pesticide multi-residue analysis of pyrethroid on green beans of Gayo Arabica coffee using the Gas Chromatography-Electron Capture Detector (GC-ECD) method was carried out. Coffee samples were taken at three locations in Bener Meriah Regency, namely Bandar, Permata, and Wih Pesam. The pyrethroid residues measured were cypermethrin, deltamethrin, and permethrin. The coffee samples were extracted by QuEChERS using a solvent of 1% acetic acid in acetonitrile. The validation parameters tested included selectivity, linearity, Limit of Detection (LoD), Limit of Quantification (LoQ), precision, and accuracy. The results showed that this method was selective, with only three pyrethroid peaks detected. The method was linear in the concentration ranges of 0.01-0.30 μg/mL, with the correlation coefficient of ≥0.99 for all samples. The sensitivity was excellent with LoD and LoQ of 0.0151-0.0420 μg/mL and 0.0504-0.1400 μg/mL. The accuracy and precision were very well with %recovery and % RSD of 83.85-105.19 and 1.5-8.3 for cypermethrin, 75.17-89.34, and 2.0-11.7 deltamethrin, and 83.16-109.43 and 3.1-3.6 for permethrin, respectively. The method application showed that no pyrethroid residues were found in all coffee samples. The result was confirmed by the obtained % recovery in ranges of 90-109 % for all samples.